A single-pulsed electromagnetic field enhances collagen synthesis in tendon cells. (March 2020) - Lin, Chih-Chun; Wu, Po-Ting; Chang, Chih-Wei; Lin, Ru-Wei; Wang, Gwo-Jaw; Jou, I-Ming; Lai, Kuo-An
Highlights: SPEMF exposure significantly up-regulated tenogenic gene expression and down-regulated inflammatory gene expression in tenocytes. SPEMF stimulation daily for 3 min significantly increased the protein synthesis of collagen type I and total collagen in 5 days. Under pro-inflammatory cytokine (IL-1β) irritation, the decreased expression of Col1a1/Col3a1 was up-regulated by SPEMF treatment, and the increased expression of Mmp1 was also reversed. SPEMF that enhances matrix synthesis and reduces matrix degeneration may counteract the imbalance in tendinopathy and be developed as a potential future strategy in tendon disorders. Abstract: Tendinopathy is a progressive pathology of tendon that is characteristic of imbalance between matrix synthesis and degeneration and is often caused by failure to adapt to mechanical loading. Non-steroidal anti-inflammatory medications (NSAIDS) are used as a conventional treatment to alleviate pain and swelling in the short term, but the ideal treatment for tendinopathy remains unclear. Here, we show a single pulsed electromagnetic field (SPEMF, 0.2 Hz) that up-regulated tenogenic gene expression (Col1a1, Col3a1, Scx, Dcn) and down-regulated inflammatory gene expression (Mmp1) in vitro . After five days of SPEMF stimulation (3 min/day), the collagen type I and total collagen synthesis protein levels were significantly increased. Under pro-inflammatory cytokine (IL-1β) irritation, the decreased expression of Col1a1/Col3a1 was up-regulated by SPEMF treatment, and the increased expression of Mmp1 was also reversed. From the above, it can be inferred that SPEMF that enhances matrix synthesis and reduces matrix degeneration may counteract the imbalance in tendinopathy. SPEMF application may be developed as a potential future strategy for therapeutic intervention in tendon disorders.